A Case Study on Legacy Information Systems Migration: A Fault Tolerant Approach - Herrera, Rafael de Paula; Felinto, Alan Salvany (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2014: Anais do X Simpósio Brasileiro de Sistemas de Informação, 2014)
Legacy Information Systems play key-roles on organizations development and growth. However, they can be considered as risky factor to operations chain whether they do not meet the demanding or become acting as single point of failures. In this work, we propose a migration model which is able to handle systems that depend on Relational Databases and its changes were driven through the use of a distributed middleware. We also pose how this approach was successfully applied while migrating a Legacy Information System to a Cloud Computing based infra-structure, adding fault-tolerance to its architecture as a competitive advantage, enabling the related services to be clustered and then horizontal scaled on demand. All major concerns on how the whole solution and its aggregated tools were conceived are discussed in high-level details, so them can be solely reproduced and integrated to another systems in order to achieve the same goals or improve its level of quality assurance.